Implementation of Good Governance Business Sharia (GGBS) and Its Implications for Sharia Conformity and Profitability (SCnP) Financial Performance in Sharia Commercial Banks in Indonesia - Nindi Apriani; Kusnendi Kusnendi; Firmansyah Firmansyah (Review of Islamic Economics and Finance (RIEF), 2020)
Abstract.     Financial performance is an analysis to see how a company carries out the rules of implementing finances properly and correctly. The measurement of the financial performance of Islamic banks mostly still uses conventional measurement indicators, namely profitability. This is considered less relevant because the measurement of the performance of Islamic banks should be measured based on the suitability of sharia. Sharia Conformity and Profitability is a tool that measures the integrity of a bank but still does not ignore the conventional side because the purpose of Islamic banks is to seek profit. This study aims to analyze the influence of Good Governance Business Sharia on Sharia Conformity and Profitability of Islamic Commercial Banks in Indonesia. The population in this study used all Islamic Commercial Banks (BUS) in Indonesia. The sample used was eleven Sharia Commercial Banks in Indonesia in 2012-2016. The method in this study uses explanatory research methods. The data analysis technique used is panel data regression. The results showed that the level of implementation of Good Governance Business Sharia was good enough and tended to increase. The Sharia Conformity and Profitability level of Islamic Commercial Banks in Indonesia has a high level of performance which means that the average performance is above average. The implementation of Good Governance Business Sharia (GGBS) positively affects Sharia Conformity but harms Profitability. The results have important implications for Islamic Commercial Banks and regulators regarding Good Governance Business Sharia. It should be modified as it aligns with sharia conformity but does not impact profitability. Keywords.    Financial performance, Sharia Conformity, and Profitability, Good Governance Business Sharia.